2008
DOI: 10.1093/chemse/bjn043
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Investigation of Protein Kinase C- and cGMP-Dependent Ion Channels in Cultured Olfactory Receptor Neurons of the Hawkmoth Manduca sexta

Abstract: In the hawkmoth Manduca sexta, pheromone stimuli of different strength and duration rise the intracellular Ca2+ concentration in olfactory receptor neurons (ORNs). While second-long pheromone stimuli activate protein kinase C (PKC), which apparently underlies processes of short-term adaptation, minute-long pheromone stimuli elevate cyclic guanosine monophosphate (cGMP) concentrations, which correlates with time courses of long-term adaptation. To identify ion channels involved in the sliding adjustment of olfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(32 citation statements)
references
References 27 publications
1
31
0
Order By: Relevance
“…There is evidence that NO increases cGMP concentration (Stengl et al, 2001) and activates ion channels in the ORNs of M. sexta (Zufall & Hatt, 1991;Dolzer et al, 2008). Stengl & Zintl (1996) found NADPH diaphorase activity (indicative of NO synthase activity) in ORNs and olfactory supporting cells of M. sexta.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is evidence that NO increases cGMP concentration (Stengl et al, 2001) and activates ion channels in the ORNs of M. sexta (Zufall & Hatt, 1991;Dolzer et al, 2008). Stengl & Zintl (1996) found NADPH diaphorase activity (indicative of NO synthase activity) in ORNs and olfactory supporting cells of M. sexta.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies on NO and the sensorial function in insects have used biochemical (Stengl & Zintl, 1996;Redkozubov, 2000;Newland & Yates, 2008) or electrophysiological (Stengl et al, 2001;Waserman & Itagaki, 2003;Dolzer et al, 2008) methods. However, the insect's behavioural response was only studied in a few cases, mainly in the locust (Newland & Yates, 2007;Wenzel et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…An apparently directly cAMPdependent non-specific cation channel and a cAMP-dependent Ca 2+ channel were identified in M. sexta , next to other cyclic nucleotide-sensitive cation and potassium channels (Dolzer, 2002;Dolzer et al, 2008). While these channels were specifically sensitive to 8bcAMP at concentrations lower than 1 mmol l -1 cyclic nucleotide, at considerably higher concentrations of cAMP cGMP-dependent cation channels were also activated.…”
Section: Potential Antennal Targets Of Campmentioning
confidence: 95%
“…Recently it was shown that heterologously expressed insect olfactory receptors form cAMP-sensitive ligand-gated ion channel complexes, with the highly conserved chaperone protein OR83b (Sato et al, 2008;Wicher et al, 2008). Furthermore, cyclic nucleotide-sensitive ion channels were characterized in patch clamp recordings of cultured ORNs of Manduca sexta (Dolzer et al, 2008;Krannich and Stengl, 2008). Preliminary biochemical experiments indicate that cyclic nucleotide concentrations express time-dependent rhythms in insect antennae (W. Peters, T. Schendzielorz and M.S., unpublished).…”
Section: Introductionmentioning
confidence: 99%
“…Next, a possible dependence of the BAL response on PLC or PKC activity was examined, as reported previously for hawkmoth pheromone transduction (Stengl, 1993(Stengl, , 1994(Stengl, , 2010Dolzer et al, 2008) and for fruitfly Orco (Sargsyan et al, 2011;Getahun et al, 2013). Thus, Ca 2+ imaging experiments were performed in HEK293 cells expressing MsexOrco and MsexOr1.…”
Section: Plc-and Pkc-dependent Regulation Of Bal Responses In Heterolmentioning
confidence: 99%